One-pot synthesis of cubic PtPdCu nanocages with enhanced electrocatalytic activity for reduction of H2O2. Issue 54 (6th July 2017) - Tian, Liangliang; Chen, Yanling; Wu, Shenping; Cai, Yanhua; Liu, Hongdong; Zhang, Jin; Yang, Cong; He, Gege; Xiao, Wei; Li, Lu; Lin, Li; Cheng, Yue
Abstract : Cubic PtPdCu nanocages were prepared using Cu2 O as sacrificial templates and applied to detect H2 O2 . PtPdCu nanocages exhibit high sensitivity at a low potential of 0.05 V. The high activity is related to the hollow structure and synergistic effect. Abstract : Despite the high electrocatalytic activity of Pt, pure Pt electrocatalysts always suffer from high cost and poor poison resistance. In this work, a cubic PtPdCu nanocage (NC) trimetallic electrocatalyst was synthesized using cuprous oxide as a sacrificial template. Being employed as a H2 O2 detection electrode, PtPdCu NCs exhibit higher sensitivity (562.83 μA mM −1 cm −2 ) than that of PdCu NCs (210.19 μA mM −1 cm −2 ), PtCu NCs (411.34 μA mM −1 cm −2 ) and commercial Pt black (16.94 μA mM −1 cm −2 ). Furthermore, a PtPdCu NCs electrode presents a working potential as low as 0.05 V. The excellent electrocatalytic activity can be attributed to the suitable hollow porous structure and synergistic electrocatalysis effect between Pt, Pd and Cu. It is believed that the trimetallic PtPdCu NCs electrocatalyst has potential applications in the design of H2 O2 detection electrodes.